Legal Protection for Buildings with Traditional Architecture in the Modern Era of Bali - I Putu Andika Pratama; I Made Artana; Nathan Franklin; Ni Made Anggia Paramesthi Fajar; Putu Chandra Kinandana Kayuan (Universitas Muhammadiyah Malang, 2023)
Along with the times, Balinese traditional architecture is increasingly being eroded by modern architectural art and also by the occurrence of damages. The purpose of this paper is to analyze the protection of traditional architectural buildings in the modern Balinese era and problems related to the preservation of traditional architecture in the modern Balinese era. This research adopts the doctrinal research and uses primary, secondary and tertiary legal materials. These legal materials were collected using a card system with a statute approach, a fact approach, and an analytical conceptual approach. Findings of the study show that: first, according to national law, Balinese traditional architecture is a cultural heritage and is regulated in Indonesian Law Number 5 of 1992 concerning Cultural Heritage Objects. Meanwhile, in the Province of Bali, Balinese traditional architecture is regulated in the Regional Regulation of the Province of Bali Number 5 of 2005 concerning Architectural Requirements for Buildings; secondly, one of the ways taken by the Government of Bali Province to preserve Balinese traditional architecture is to apply it to buildings. Balinese architecture, besides being used in the physical form of buildings, is also applied to the design of fences and gates along the main roads and streets in the environment. Balinese architecture is also required to be applied to government-owned houses or buildings, and official residences. Abstrak Arsitektur tradisional Bali seiring perkembangan jaman semakin tergerus oleh seni arsitektur modern dan juga terjadinya kerusakan-kerusakan. Tujuan penulisan ini adalah menganalisis perlindungan bangunan arsitektur tradisional di era Bali modern dan permasalahan terkait pelestarian arsitektur tradisional di era Bali modern. Penelitian ini merupakan Doctrinal Research dengan menggunakan bahan hukum primer, sekunder dan tersier. Teknik pengumpulan bahan hukum dilakukan dengan sistem kartu dengan pendekatan perundang-undangan, pendekatan fakta, dan pendekatan analisis konseptual. Hasil dari penelitian ini yaitu: Pertama, Secara hukum nasional, arsitektur tradisional Bali merupakan salah satu cagar budaya dan diatur di dalam Undang-Undang Nomor 5 Tahun 1992 tentang Benda Cagar Budaya. Sedangkan di Provinsi Bali, arsitektur tradisional Bali telah diatur di dalam Peraturan Daerah Provinsi Bali Nomor 5 Tahun 2005 tentang Persyaratan Arsitektur Bangunan Gedung; kedua, Salah satu cara yang dilakukan oleh Pemerintah Provinsi Bali untuk pelestarian arsitektur tradisional Bali adalah dengan mengaplikasikannya pada bangunan gedung. Arsitektur Bali selain digunakan dalam bentuk fisik dari bangunan gedung, juga diberlakukan untuk desain pagar dan gerbang disepanjang jalan raya dan jalan lingkungan. Arsitektur Bali juga diwajibkan untuk digunakan terhadap bangunan atau gedung milik pemerintah, rumah dinas maupun rumah jabatan.